„Znane” i nieznane produkcje przedwojennego polskiego kina. Halka Konstantego Meglickiego i Sportowiec mimo woli Mieczysława Krawicza - Pieńkowski, Michał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2017)
There are many Polish films from the pre-war period that are not known to the public today. Most oft en they simply did not make it to modern times or only fragments are preserved, their condition too poor to allow utilization. One of such films is Halka, directed by Konstanty Meglicki in 1929, which due to digital restoration has returned to the screen in November 2016, after decades-long break. In recent years, however, it’s been discovered that even some seemingly well-known films should in fact be considered unknown. Due to the research conducted at the National Film Archives, new facts came to light, revealing lost film fragments or alternative versions. One such example is a film from 1939 called Sportowiec mimo woli, until now only known for its post-war American adaptation, turns out to be very different from the unknown original version. Polish pre-war cinema, which was often treated with some disdain, is now perceived in a very different light. And recent discoveries allow us to re-examine the achievements of the early period of Polish cinematography.